KADAR MINUMAN BERALKOHOL PERDA NOMOR 7 TAHUN 1953 KOTA YOGYAKARTA PERSPEKTIF MAQĀSID ASY-SYARĪ’AH - Idawan, Irman Doni (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
In terms of permits and collection of sales tax on licenses to sell liquor, Yogyakarta city government has issued Regional Regulation (Perda) No. 7 of 1953 and confirmed by the Regional Regulation No. 7 of 2006 on changes to the criminal provisions in local regulations area of the city of Yogyakarta. However, these two rules are not discussed in detail the levels of restrictions in the use of alcohol liquor is allowed to be sold. This paper uses philosophical worldview that explains the theory of Maqa>sid as-Syari>’ah in understanding the limitations alcoholic liquor contained in the Regional Regulation No. 7 of 1953. The regulation is not clear on setting the levels of alcohol restrictions. In fact, the provision of alcohol it is a very crucial due to excess use of alcohol is a risk to the maintenance of religion, life, intellect, lineage and property. New legislation, number 7 in 2006 only stipulates sanctions for violations contained in the Regional Regulation No.. 7 in 1953 and have not been able to address problems that exist.